Detection of in-plane fiber waviness in cross-ply CFRP laminates using layer selectable eddy current method. (March 2016) - Mizukami, Koichi; Mizutani, Yoshihiro; Kimura, Kenshi; Sato, Akiyoshi; Todoroki, Akira; Suzuki, Yoshiro
Abstract: This paper presents an eddy current testing method to detect in-plane fiber waviness in cross-ply carbon fiber reinforced plastic (CFRP) laminates. We propose a method which has high sensitivity to presence of in-plane waviness and can select layers to be inspected. The probe was used to detect artificially induced in-plane waviness in cross-ply CFRP laminates. It was observed that obtained signal has extreme value at the edges and vertex of the waviness, which implies the possibility of precise identification of waviness location. Detectability of subsurface waviness was investigated using 20 layer cross-ply laminate with in-plane waviness at different depths. Experimental results showed that in-plane waviness 18 layers away from the surface could be detected. The minimum misalignment angle of the detected waviness was 7.4°. The effectiveness of the probe and physical background of the obtained signals were verified by finite element method analyses.